The Relationship between Educational Technology Integration, Classroom Management, and Student-Centred Learning on Teaching Effectiveness and Student Learning Outcomes in Indonesian - Irwanto Irwanto (West Science Social and Humanities Studies, 2024)
This study investigates the relationship between educational technology integration, classroom management, and student-centred learning on teaching effectiveness and student learning outcomes in Indonesian schools. Utilizing a quantitative analysis approach, data were collected from 285 teachers through a structured questionnaire employing a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) to test the proposed hypotheses. The findings indicate that all the examined relationships are both positive and significant. Specifically, integrating educational technology is shown to enhance teaching effectiveness and improve student learning outcomes. Additionally, effective classroom management positively influences teaching effectiveness and fosters a student-centred learning environment, which in turn leads to better student learning outcomes. These results highlight the critical role of technology integration, effective classroom management, and student-centred learning in boosting teaching effectiveness and student achievement in Indonesian schools. The study offers valuable insights for educators, policymakers, and stakeholders looking to enhance educational practices through the strategic implementation of these components.